Penyuluhan Inovasi Mie Sehat Tanpa Pengawet Bagi Ibu Rumah Tangga di Kelurahan Sidomulyo Kecamatan Medan Tuntungan - Anna Angela Sitinjak; Dimas Frananta Simatupang (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2021)
Community service activities (CSA) have been carried out using lecture methods, discussions, and practices regarding innovations in making healthy noodles without preservatives to provide information, knowledge, and skills regarding innovations in making healthy food and encourage and increase entrepreneurship homemakers. The innovation of making healthy noodles with ingredients without preservatives is considered vital because it is beneficial for health and as a step to utilize natural ingredients obtained in the surrounding environment. This activity was attended by 20 housewives in Sidomulyo Village, Medan Tuntungan District, Medan City, North Sumatra Province with different knowledge backgrounds. The CSA training that has been carried out provides understanding and skills to homemakers in processing natural ingredients into healthy food and can increase the economy because it can be commercialized. This CSA training also received a positive response from participants because it could practice directly, and the team provided the freedom to express opinions and develop ideas during the activity. This service activity was considered very useful as much as 65% and use as much as 35% of the questionnaire results distributed during the implementation of the activity. Through this CSA activity, it is hoped that the active role of participants in distributing knowledge and skills to the community in the surrounding environment is expected.